Sea-level response to melting of Antarctic ice shelves on multi-centennial timescales with the fast Elementary Thermomechanical Ice Sheet model (f.ETISh v1.0) - Pattyn, Frank (2017)
The magnitude of the Antarctic ice sheet's contribution to global sea-level rise is dominated by the potential of its marine sectors to become unstable and collapse as a response to ocean (and atmospheric) forcing. This paper presents Antarctic sea-level response to sudden atmospheric and oceanic forcings on multi-centennial timescales with the newly developed fast Elementary Thermomechanical Ice Sheet (f.ETISh) model. The f.ETISh model is a vertically integrated hybrid ice sheet-ice shelf model with vertically integrated thermomechanical coupling, making the model two-dimensional. Its marine boundary is represented by two different flux conditions, coherent with power-law basal sliding and Coulomb basal friction. The model has been compared to existing benchmarks. Modelled Antarctic ice sheet response to forcing is dominated by sub-ice shelf melt and the sensitivity is highly dependent on basal conditions at the grounding line. Coulomb friction in the grounding-line transition zone leads to significantly higher mass loss in both West and East Antarctica on centennial timescales, leading to 1.5 m sea-level rise after 500 years for a limited melt scenario of 10 m ag-1 under freely floating ice shelves, up to 6 m for a 50 m ag-1 scenario. The higher sensitivity is attributed to higher ice fluxes at the grounding line due to vanishing effective pressure. Removing the ice shelves altogether results in a disintegration of the West Antarctic ice sheet and (partially) marine basins in East Antarctica. After 500 years, this leads to a 5 m and a 16 m sea-level rise for the power-law basal sliding and Coulomb friction conditions at the grounding line, respectively. The latter value agrees with simulations by DeConto and Pollard (2016) over a similar period (but with different forcing and including processes of hydrofracturing and cliff failure). The chosen parametrizations make model results largely independent of spatial resolution so that f.ETISh can potentially be integrated in large-scale Earth system models. ...